Analysis of Road Safety Based on Road Type on National Roads in Bali Province - Maulidya, Fairuz Sasqia; Widyastuti, Hera (CIVED, 2024)
The Province of Bali is one of the most popular tourist destinations in Indonesia which accounts for 40% of tourist visits in Indonesia. Apart from being a tourist spot, Bali also often hosts various state events. As a destination that is often in the public and world spotlight, it is important for Bali to have safer road infrastructure. However, based on data in the field, there are still many accidents that occur on National Roads in Bali and even tend to increase. If this is not handled, the impact will also be a problem in various aspects. This research aims to analyze road safety based on the type of road using the accident rate and fatality rate method on National Road sections in Bali Province. Based on the results of data analysis, this research shows the results of data accident rate or the highest accident rate is 160 incidents per 1 million vehicles per year on the Kosamba – Angentelu Bali road section. For data analysis of fatality rate or death rate, the highest is 245 per 1 million vehicles per year on Jalan A.Yani (Amlapura) Bali. And the type of road that has the highest accident rate and fatality rate number is the 2/2 UD road type.